\(1\)st term \(= 1\) (given)

\(2\)nd term \(= 1 + 4 = 5\)

\(3\)rd term \(= 5 + 4 = 9\)

We have \(5\) ans choices each expression contains \(n\) which is the number of terms

Equating each expression with a term in our sequence should give us the ans

let us suppose 2nd term which is \(5\)

Among the ans choices whichever returns with a value for \(n = 2\) is the ans

option c does exactly that when \(4n -3 =5\)

or, \(4n = 8\) hence, \(n = 2\)

option c

_________________

This is my response to the question and may be incorrect. Feel free to rectify any mistakes